Preoperative Immunonutrition and Postoperative Outcomes in Radical Pancreaticoduodenectomy Patients - , Murat Aba, Ahmet Gökhan Sarıtaş, Burak Yavuz, Kubilay Dalcı, Abdullah Ülkü, Atılgan Tolga Akçam (Turkish Journal of Gastroenterology 1, 2023)
Background/Aims: This study aimed to compare the patient groups who received and did not receive immunonutrition in terms of mortality and morbidity in patients who underwent radical pancreaticoduodenectomy. Materials and Methods: Two groups were formed from 40 patients who underwent radical pancreaticoduodenectomy in our clinic in 2021. The patients in study group were given enteral immunonutrition support for 5 days preoperatively. For this purpose, a standard enteral immunonutrition product containing arginine, omega-3 fatty acids, and RNA (dietary nucleotides) was used. Patients’ data of demographical, laboratory, postoperative complications, and current clinical status were analyzed. Result: Mortality developed in 5 (25 %) patients in the treatment group and 4 (20 %) patients in the control group in the following months (P > .05). The estimated survival rate in the treatment group was 21.8 ± 2.8 months in the treatment group 19.1 ± 1.7 months in the control group (P > .05). The length of hospital stay was 12.89 ± 3.3 days in the treatment group, while it was 16.47 ± 6.83 days in the control group (P < .05). In the postoperative follow-ups, delayed gastric emptying symptoms developed in 3 patients in the treatment group, while the same complication was observed in 9 patients in the control group (P < .05). Surgical site infections occurred in 4 patients in the treatment group and 9 patients in the control group (P < .05). Conclusion: It was observed that preoperative oral immunonutrition before pancreaticoduodenectomy was effective in reducing the risk of delayed gastric emptying after surgery and the length of hospital stay. Cite this article as: Aba M, Sarıtaş AG, Yavuz B, Dalcı K, Ülkü A, Akçam AT. Preoperative immunonutrition and postoperative outcomes in radical pancreaticoduodenectomy patients. Turk J Gastroenterol. 2024;35(1):32-40.